Could We Be Marsupials? Very Premature Babies and Artificial Wombs - Davis, Dena S. (The Hastings Center report, 2019)
It is often pointed out that one cannot be “a little bit pregnant,” but pregnancy’s borders are no longer so crisp. At Children’s Hospital of Philadelphia, scientists have created an artificial womb in which “extremely premature” lambs were nurtured for four weeks, enough to make them ready to meet the world. The goal is to advance this technology until it is available for very premature human infants. At present, we put preemies into neonatal intensive care units, which are extremely stressful for the babies and their families, and the things we do to try to support them often cause serious damage. If successful, the artificial womb could be a terrific technology. The implications are remarkable. Would humans become somewhat like marsupials? Now, one is either born or not. Would this technology create a new, intermediate stage? What would this mean ethically and legally?